(untitled) (Medical Forum Monthly, 2026)
Objective: To determine the frequency of endometrial carcinoma among women presenting with abnormal uterine bleeding at a secondary care hospital. Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Gynecology and Obstetrics, Maqsood Medical Complex, Peshawar, from 1st March 2025 to 28th February 2026. Methods: The number of women, who presented with abnormal uterine bleeding, were included in the study by non-probability consecutive sampling, totalling 247 women. Information about age, parity, menopausal status, bleeding pattern, comorbidities, endometrial thickness and histopathological diagnosis were recorded. Biopsy, dilatation and curettage or hysterectomy specimen provided the source of endometrial tissue when clinically indicated. Results: The mean age of patients was 44.8 ± 10.7 years. Mean duration of symptoms was 5.9 ± 3.4 months. Heavy menstrual bleeding was the most common presentation 93 (37.7%). Overall, 13 patients were diagnosed with the endometrial carcinoma, with a frequency of 5.3%. Bleeding pattern, endometrial thickness, age, post-menopausality, diabetes mellitus, hypertension and obesity were significantly associated with carcinoma. Conclusion: A significant number of women with abnormal uterine bleeding were found to have endometrial carcinoma. Older age, postmenopausal bleeding, and elevated endometrial thickness and metabolic comorbidities should lead to prompt evaluation of the endometrium and subsequent histopathological confirmation.